'A big night out': Young people's drinking, social practice and spatial experience in the 'liminoid' zones of English night-time cities. (February 2015) - Roberts, Marion
This paper frames the debate on 'binge' drinking amongst young people within the perspectives of materialism and cultural geography. Drawing on the concept of social practice as interpreted through the perspective of urban design, the research investigated spatial variations in youth drinking using a case study approach to examine two urban areas in England. The study confirmed that the social practice of the 'big night out' has become an established feature of youth drinking. The research found the practice constituted in specialist 'clusters' of venues and it is argued that place-based characteristics form a significant component of its production and experience. The paper concludes with a reflection on the challenges the evidence poses to previous interpretations of leisure divisions within mainstream nightlife and to the theorisation of place-based differences in drinking milieux oriented towards young people. The implications for public policies are considered.